A genetic algorithm based Pareto optimization hedge-algebra-based fuzzy rules-sets - Hồ, Nguyễn Cát; Sơn, Trần Thái; Long, Dương Thăng; Hùng, Trần Duy (Journal of Computer Science and Cybernetics, 2012)
See full text.